2011
DOI: 10.1165/rcmb.2010-0029oc
|View full text |Cite|
|
Sign up to set email alerts
|

Asthmatic Airway Epithelium Is Intrinsically Inflammatory and Mitotically Dyssynchronous

Abstract: Asthma is an inflammatory condition for which anti-inflammatory glucocorticoids are the standard of care. However, similar efficacy has not been shown for agents targeting inflammatory cells and pathways. This suggests a noninflammatory cell contributor (e.g., epithelium) to asthmatic inflammation. Herein, we sought to define the intrinsic and glucocorticoid-affected properties of asthmatic airway epithelium compared with normal epithelium. Human primary differentiated normal and asthmatic airway epithelia wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
61
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 49 publications
5
61
1
2
Order By: Relevance
“…Both the asthmatic grafted epithelium and the asthmatic human lung biopsy tissue show decreased E-cadherin expression. This is all consistent with our previous work showing that, when differentiated at air-liquid interface culture, asthmatic-derived epithelial cells are less differentiated in comparison to nonasthmatic-derived cells, as demonstrated by increased basal cell number and lack of E-cadherin (5,6,11,19).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Both the asthmatic grafted epithelium and the asthmatic human lung biopsy tissue show decreased E-cadherin expression. This is all consistent with our previous work showing that, when differentiated at air-liquid interface culture, asthmatic-derived epithelial cells are less differentiated in comparison to nonasthmatic-derived cells, as demonstrated by increased basal cell number and lack of E-cadherin (5,6,11,19).…”
Section: Discussionsupporting
confidence: 93%
“…We and others (6,11,41) have shown previously that basolateral secretion of TGF-b1 is increased from asthmatic airway epithelium in vitro. The current study furthers that work by demonstrating increased TGF-b1 in asthmatic xenografts, an in vivo system.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…After 14-21 days (EpiAirway) or 20-45 days (MucilAir) of culture the epithelia are fully ciliated and electrically tight (TEERā‰ˆ450 Ī© cm 2 ). EpiAirway cultures are available in a number of useful insert formats, and have been successfully utilized for numerous applications including airway drug delivery (Agu et al, 2006;Leonard et al, 2005Leonard et al, , 2007, airway disease modelling (Bai et al, 2015;Freishtat et al, 2011; ALI cultures have provided insights into pathogenetic mechanisms, for example the ability of Th2 cytokines, IL-4 and IL-13, to skew bronchial epithelial cell differentiation towards goblet cell hyperplasia, increased mucin gene expression and mucous hypersecretion (Kanoh et al, 2011;Thavagnanam et al, 2011;Zuyderduyn et al, 2011). Furthermore, use of ALI cultures has allowed for comparisons of barrier properties, mucus production and other responses of epithelial cells from asthmatic and healthy subjects, as well as the demonstration that tight junctions are reduced and mucus production and inflammatory cytokine induction are increased in cultures from asthmatic subjects (as observed in vivo).…”
Section: Fully Differentiated 3d Human Airway Epithelial Modelsmentioning
confidence: 99%
“…Furthermore, use of ALI cultures has allowed for comparisons of barrier properties, mucus production and other responses of epithelial cells from asthmatic and healthy subjects, as well as the demonstration that tight junctions are reduced and mucus production and inflammatory cytokine induction are increased in cultures from asthmatic subjects (as observed in vivo). Such changes have been seen to correspond to an increase in ionic and macromolecular permeability (Xiao et al, 2011;Bai et al, 2015;Freishtat et al, 2011;Watson et al, 2010). It has also been shown that the permeability of the bronchial epithelial cell layer is only increased in asthmatic subjects after exposure to ozone or nitrogen dioxide (Bayram et al, 2002), and that mediator release is altered after exposure of ALI cultures from asthmatic donors to respiratory syncytial virus (RSV) or particulate matter (Hackett et al, 2011b).…”
Section: Fully Differentiated 3d Human Airway Epithelial Modelsmentioning
confidence: 99%